PENGARUH KONSENTRASI HORMON Indole Butyric Acid (IBA) dan WADAH PENANAMAN TERHADAP KECEPATAN TUMBUH TUNAS STEK AKAR CENDANA (Santalum album) PADA MEDIA TANAH - , ARUM LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sandalwood is native to Indonesia, especially in East Nusa Tenggara Islands. This plant has a high economic value. The original area sandalwood plants have already become extinct, resulting in the construction of these plants require forest seedlings with good quality. One attempts to hold sandalwood seedlings is conducting vegetative propagation using cuttings root. This study aims to determine the effect of hormone IBA fatherly and containers that are used in growing medium such as soil. Research design used was a completely randomized design with 2 factors, namely testing the first hormonal factors with a concentration IBA of 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, and 1000 ppm. The second factor is the container being used for planting cuttings in the form of baskets and clay pots. Parameters observed were the early growth of shoots, number of shoots, shoots color, and percentage of live shoots. The results showed that sandalwood can be propagated using root cuttings. IBA hormone treatment and planting container affect the speed of growth of sandalwood root cuttings. From observations with the soaking time 20 minute, the cuttings were give hormone concentration 200 ppm gives the best resul ts in the number of shoots, shoots beginning to grow compared to control and other concentrations. Hormone concentration of 200 ppm is considered optimum in shoot growth of cendana root cuttings. The best planting container in the form if pots made of clay.